Risk factors of prolonged mechanical ventilation following open heart surgery: what has changed over the last decade? - Siddiqui, Muhammad-Mujtaba Ali; Paras, Iftikhar; Jalal, Anjum (Cardiovascular Diagnosis and Therapy, 2012)
Objective: To identify the risk factors for prolonged invasive mechanical ventilation after open heart surgery in Pakistan. Design: This study is based on retrospective analysis of database. Place and duration: We conducted study of all patients who underwent open heart surgery at CPE Institute of Cardiology, Multan from March 2009 to May 2011. Patients & methods: The data was retrieved from the database in the form of electronic spreadsheet which was then analyzed using SPSS software. The patients with incomplete data entries were removed from the analysis resulting in a set of 1,617 patients The data of each patient consisted of 65 preoperative, operative and postoperative variables. The data was summarized as means, medians and standard deviations for numeric variables and frequencies and percentages or categoric variables. These risk factors were compared using Chi-sqaure test. Their ODDs ratios and 95% confidence intervals of ODD’s Ratios and P values were calculated. Results: Out of a total of 1,617 patients, 77 patients (4.76%) had prolonged ventilation for a cumulated duration of more than over 24 hours. Preoperative renal failure, emphysema, low EF (